A monocentric analysis of the efficacy of extracellular cryoprotectants in unfrozen solutions for cleavage stage embryos - Francesco Capodanno; Jessica Daolio; Gaetano De Feo; Angela Falbo; Daria Morini; Alessia Nicoli; Luca Braglia; MariaTeresa Villani; Giovanni B. La Sala; Lodovico Parmegiani; Lorenzo Aguzzoli (BMC, 2019)
Abstract Background In the absence of international guidelines indicating the usage of vitrification rather than slow-freezing, the study aim was to analyze a large cohort of slow-frozen/thawed embryos to produce a rationale supporting the standardization of IVF cryopreservation policy. Methods This retrospective analysis included 4779 cleavage stage embryos cryopreserved by slow-freezing/thawing from September 2009 to April 2017 at a single Center. Biological and clinical outcomes of three different commercial kits adopted sequentially, i.e. Vitrolife Cleave Kit® from Vitrolife (kit 1) vs. K-SICS-5000 Kit® and K-SITS-5000 Kit® from Cook Medical (kit 2) and Freeze/Thaw 1™ Kit® from Vitrolife (kit 3) were collected and compared in the light of cryoprotectants composition. Results Kit 3 compared to kit 1 and kit 2 showed significantly (P < 0.001) higher embryo survival (79.9% vs. 75.6 and 68.1%, respectively) and frozen embryo replacement (91.5% vs. 86.5 and 83.3%, respectively) rates, and significantly (P < 0.001) lower blastomere degeneration rate (41.5% vs. 43.6 and 52.4%, respectively). No significant difference for clinical outcomes was observed among kits. Only a slight positive trend was observed for kit 3 vs. kit 1 and kit 2 on delivery rate per thawing cycle (7.12% vs. 4.19 and 4.51%, respectively; P < 0.058) and live birth rate (3.07% vs. 2.59 and 1.93%, respectively, P < 0.069). Thawing solutions of kit 3 were similar to those of any warming protocol. Conclusions A defined concentration of extracellular cryoprotectants in thawing/warming solutions had a beneficial effect on the embryo cryosurvival rate. Results could provide the rationale for the adoption of a single standardized warming protocol.